PROFILING SENSORY PADA PRODUK COKELAT PT. KAKAO BHINNEKA SEJAHTERA (MOODCO FINE CHOCOLATE) DENGAN METODE RATE-ALL-THAT-APPLY (RATA) - Qonnitasya, Athira; Damat, Damat; Wahyudi, Vritta Amroini (Universitas Muhammadiyah Malang, 2023)
Chocolate is a processed food product based on cocoa beans which is processed using a machine. Differences in processing raw materials can produce different sensory characteristics that can affect consumer preferences. In this study, sensory descriptive analysis was carried out using the Rate-All-That-Apply (RATA) method to determine sensory profiles and to determine differences in sensory attributes of white chocolate (Kokoken Gulo Kaluku), milk chocolate (Arai), and dark chocolate (Idi' Cara'de). Based on the results, there are 4 attributes that are the same in each chocolate variant, namely glossy, snap, hardness, and mouthfeel melting. Kokoken Gulo Kaluku and Arai have the highest intensity on the mouthfeel melting attribute, while Idi' Cara'de has the highest intensity on the glossy attribute.